Financial Services and Trade Agreements in Latin America and the Caribbean : An Overview - Goncalves, Marilyne Pereira; Stephanou, Constantinos (World Bank, Washington, DC, 2012)
The authors review the international framework governing trade in financial services, describe the treatment of financial services in recent trade agreements involving Latin America and Caribbean countries, and analyze the liberalization commitments made in three selected country case studies-Chile, Colombia, and Costa Rica. They give emphasis to free trade agreements because of the generally deeper level of liberalization and rule-making achieved to-date. The authors discuss some of the causes and potential implications of their findings.